A luz e o movimento no processo de criação da iluminação cênica para a dança - Jacinto, Rafael Cardoso (2024)
This research examines the relationship between undergraduate Dance students at the Federal University of Santa Maria (UFSM) and stage lighting within their poeticcreative processes. The study seeks to understand how this interaction influences artistic expression and the development of the students’ creative works. In this sense, it contributes to the broader discussion on the inclusion of stage lighting in dance education by analyzing its impact on creative processes and proposing pathways for an integrated approach to light and movement. By analyzing students’ perceptions, practices, and techniques, the research investigates the effects of stage lighting on the aesthetics and narrative structures of performances. It also identifies the challenges and opportunities encountered by students as they incorporate lighting into their artistic projects. Furthermore, the study proposes practical guidelines—developed through hands-on workshops—to enhance students’ engagement with stage lighting in their creative productions, fostering a deeper understanding and more effective application of lighting as a language within the performing arts. Methodologically, this qualitative research is inspired by a case study approach and employs mixed data collection tools, including observation and direct participation. Data production was carried out through dialogue and the creation of scenic materials during class meetings, using the study of lighting as a starting point. To achieve a more precise and comprehensive understanding of the various elements of the research, the following authors were used as theoretical references: Yaron Abulafia (2015), Adolphe Appia (1899), Eduardo Tudella (2017), Edward Gordon Craig (1911), Richard Dunham (2018), and Stanley Russell McCandless (1958), among others.The study concludes that it provides valuable contributions to the educational and artistic fields, as well as to the visual studies of the performing arts, offering opportunities for meaningful discoveries and reflections on lighting and dance.